Foundations and Practice of Security 13th International Symposium, FPS 2020, Montreal, QC, Canada, December 1–3, 2020, Revised Selected Papers - Nicolescu, Gabriela; Tria, Assia; Fernandez, José M.; Marion, Jean-Yves (Cham Springer International Publishing, 2021)
This book constitutes the revised selected papers of the 13th International Symposium on Foundations and Practice of Security, FPS 2020, held in Montréal, QC, Canada, in December 2020. The 11full papers and 1 short paper presented in this book were carefully reviewed and selected from 23 submissions. They cover a range of topics such as Analysis and Detection; Prevention and Efficiency; and Privacy by Design
New Wrapper Feature Selection Algorithm for Anomaly-based Intrusion Detection Systems -- Network Security for Home IoT Devices Must Involve the User: a Position Paper -- A quantitative security risk analysis framework for modelling and analyzing advanced persistent threats -- An analysis of the use of CVEs by IoT malware -- A Priority-based Domain Type Enforcement for Exception Management -- Developer-Proof Prevention of SQL Injections -- A Survey of Advanced Encryption for Database Security: Primitives, Schemes, and Attacks -- Fast Short and Fast Linear Cramer-Shoup -- Anonymous proof-of-asset transactions using designated blind signatures -- Modeling Attacks and Efficient Countermeasures on Interpose PUF -- Error-Free Lattice-Based Key Encapsulation Mechanism Based on Ring-LWE -- Pisces: A New Zero-Knowledge Protocol for Blockchain Privacy
Keywords: Data protection; Data and Information Security